A highly soluble, crystalline covalent organic framework compatible with device implementation. Issue 4 (15th November 2018) - Wang, Lingling; Zeng, Cheng; Xu, Hong; Yin, Panchao; Chen, Dongcheng; Deng, Jian; Li, Mu; Zheng, Nan; Gu, Cheng; Ma, Yuguang
Abstract : We report a soluble yet crystalline covalent organic framework (COF) by regulation of inter-layer interactions, which endows the COF with remarkable solubility and processability of thin films for optoelectronic devices that exhibit high yet anisotropic conductivities and outperform all the other COF-based semiconductors. Abstract : Covalent organic frameworks (COFs) have emerged as a tailor-made platform for designing next-generation two-dimensional materials. However, COFs are produced as insoluble and unprocessable solids, which precludes the preparation of thin films for optoelectronic applications. Here, we report designed synthesis of a highly soluble yet crystalline COF material through the regulation of its inter-layer interactions. The resulting COF is remarkably soluble in a variety of organic solvents and forms stable true solutions with retention of its layered structure. These unique features endow the COF with solution processability; high-quality, large-area COF films can be produced on various substrates in a high-throughput and efficient manner, with good control over the film thickness, making this material compatible with a variety of device applications. The films are electrically anisotropic; the intra-layer carrier conduction is inhibited, while the inter-layer carrier migration is outstanding, showing the highest conductivity among all reported COF materials. Our highly soluble and processable COF may open new pathways for realising high-performance COF-based optoelectronic devices with diverse functions.